Pengaruh Kepemilikan Keluarga Dalam Memoderasi Dewan Direksi Wanita Dan Komite Audit Wanita Terhadap Manajemen Laba - Cing Mei; Mardianto Mardianto (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
Agency theory explains the relationship between investors and management in which more information is owned by management, so it is often misused as an encouragement to engineer earnings according to their interests, which are known as earnings management. The purpose of the study was to examined the influence of female board of directors, female independent directors, and female audit committee on earnings management. In addition, also examined family ownership as moderation in the relationship of female board directors, female independent directors, female audit committee on earnings management. This study uses a quantitative type approach which was analyzed using the panel regression method through the EViews application. The sample in this study was 1.220 data with a total source of 349 non-financial companies that listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2022 which were determined based on purposive sampling method. The results showed (i) the higher percentage of women on the board of directors, the lower potential earnings management practices; (ii) there are no significant relationship was found between of female independent directors and earnings management; (iii) the higher percentage of female audit committee, the lower potential earnings management practices; (iv) Family ownership as moderation can only weaken the relationship of the female board of directors to earnings management, in other words, the leadership role of women in the board of directors is not optimal in family companies.